Actions to support the entrepreneurship and university-business relationship developed by Technological Innovation Center of the Federal University of São João del-Rei (Research, Society and Development, 2022)
The role of universities is changing in the last decades to act as a facilitator of technology transfer and as an incentive for economic development locally and regionally. In this context, the attention on academic entrepreneurship increased in the areas of higher education once Universities are considered a key mechanism for new innovative advances. This study aimed to investigate and discuss the actions that a Center for Entrepreneurship and Technological Innovation of the Federal University of São João del Rei has developed to support and encourage entrepreneurial training and map the enterprises affiliated with the university in which it is located. More specifically, it was investigated the entrepreneurial training activities, business incubation and the mapping of University-related companies. The present research is characterized by an exploratory qualitative approach and uses the case study technique at a Brazilian Federal University. Despite its innovation policy being on an initial trajectory, the results show that the University created the mechanisms to promote entrepreneurship and innovation, as well as to carry out the University-Company interactions. The University studied has achieved positive results that are providing the creation of innovation arrangements such as Startup, Spin-off, Junior Companies, Incubated Companies and University-related companies.